Socio-affective Presence in e-Learning: The theoretical reference model, the development and validation of the EMPSA e-Learning measurement scale - Jézégou, Annie; Zhao, Yihuan; Déro, Moïse (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
The article outlines the development and validation process of the measurement scale for socio-affective presence in e-learning. This scale was constructed based on the theoretical model of social presence in e-learning (Jézégou, 2022). The study is based on a sample of 309 students enrolled in a fully online Master’s program in Education and Training Sciences, offered by French universities. First, an exploratory factor analysis reveals a three-factor structure with strong internal consistency. Second, a confirmatory factor analysis validates this structure and confirms the relationships between the three identified factors. The results demonstrate that this scale serves as a robust psychometric instrument for studying and analyzing socioaffective presence in e-training while opening new avenues for future research.